2012
DOI: 10.1016/j.brainres.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cholinergic mechanisms in the behavioral effects of dietary fat consumption

Abstract: Clinical reports suggest a positive association between fat consumption and the incidence of hyperactivity, impulsivity and cognitive abnormalities. To investigate possible mechanisms underlying these disturbances under short-term conditions, we examined in Sprague-Dawley rats the influence of 7-day consumption of a high-fat diet (HFD) compared to chow on anxiety, novelty-seeking and exploratory behaviors and also on acetylcholine (ACh) neurotransmission that may mediate these behaviors. The HFD consumption, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 80 publications
4
24
0
Order By: Relevance
“…Spending increased time in the relatively exposed central portion of the open field is associated with impulsivity [23], as well as reduced levels of thigmotaxis and anxiety [38]. The findings of the current study concur with increased exploration and reduced anxiety observed in male rats consuming a high-fat diet for one week [39]. Similar anxiolytic effects have been documented in both male and female rats fed a cafeteria-style diet for 8 weeks; however, the cafeteria diet reduced distance traveled in the open field [40].…”
Section: Discussionsupporting
confidence: 93%
“…Spending increased time in the relatively exposed central portion of the open field is associated with impulsivity [23], as well as reduced levels of thigmotaxis and anxiety [38]. The findings of the current study concur with increased exploration and reduced anxiety observed in male rats consuming a high-fat diet for one week [39]. Similar anxiolytic effects have been documented in both male and female rats fed a cafeteria-style diet for 8 weeks; however, the cafeteria diet reduced distance traveled in the open field [40].…”
Section: Discussionsupporting
confidence: 93%
“…It takes place supposedly using complex control mechanisms, in part also determined by the existing multiple functional morphological interrelationships of these structures. The significance of these data is further underlined by the results of recent experiments revealing that high-fat/ cholesterol diet increases plasma TG, total cholesterol, non-HDL, and HDL cholesterol levels in rodents with a subsequent activation of cholinergic processes within the PFC, along with cognitive impairments (23,25), or by demonstrating the causal role of mdPFC D1 dopamine receptors in modifying high-fat food seeking (28). It is already a textbook material that decreased TG can be due to hepatic failure, but our metabolic data -physiological level of cholesterol and lactate dehydrogenase (LDH) -do not indicate liver failure.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the recent emerging of scarce and indirect data in the literature (23,25,28), little is known yet about the involvement of prefrontal cortical neurons in the central metabolic control.…”
Section: Introductionmentioning
confidence: 99%
“…Also, maternal consumption of a fat-rich diet and being overweight during pregnancy (Dietz, 1998; Hannon, Rao, & Arslanian, 2005), which increase later consumption of and preference for fatty foods in the offspring (Fisher & Birch, 1995), is found to program other behaviors, such as anxiety, novelty seeking, and depression, which themselves are likely to promote drug use and increase vulnerability to drug abuse later in life (Bilbo & Tsang, 2010; Morganstern, Ye, Liang, Fagan, & Leibowitz, 2012; Rizzo, Silverman, Metzger, & Cho, 1997). Similar findings have been obtained in animal studies, demonstrating that in utero exposure to a fat-rich diet increases both alcohol drinking (Bocarsly et al, 2012; Cabanes, de Assis, Gustafsson, & Hilakivi-Clarke, 2000) and nicotine self-administration and seeking (Morganstern et al, 2013), while also promoting the consumption of and responding for palatable foods (Chang, Gaysinskaya, Karatayev, & Leibowitz, 2008; Naef et al, 2011; Ong & Muhlhausler, 2011).…”
Section: Introductionmentioning
confidence: 99%